Entangled photon recovery state using a fiber ring resonator incorporating an erbium-doped fiber amplifier - Suchat, Suebtarkul; Khunnam, Wanchai; Yupapin, Preecha P. (My University, 2008)
We investigate a new system of photon-entangled recovery states using a fiber ring resonator incorporating an erbium-doped fiber (EDF). We also show that states of weak entangled photons can be regenerated and recovered after circulating in the amplified fiber optic medium. The output entangled photon states can be regenerated by adjusting the polarization controller of the amplified photons. Results obtained show that such a proposed system can be used to perform the polarization entangled recovery states, and the amplified output gain can be achieved. The amplifying noise is also detected and seen on the spectrum output, which affects the entangled photon output visibility. The change in the system temperature is also investigated, which shows that entangled state walk-off compensation is required to obtain the optimum entangled photon visibility. © 2008 Society of Photo-Optical Instrumentation Engineers.
Keywords: entangled photons; quantum communication; quantum repeater; ring resonator